2014
DOI: 10.15666/aeer/1201_301307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutritiona L Quality of the Goat Milk by Grazing

Abstract: Abstract. The aim of study was to investigate the effect of grazing on the nutritional quality, such as composition, vitamins and fatty acids content of dairy goat milk. Before vegetation period, all goats were kept indoors and nutrition based on hay diet. After turn-out to pasture, all goats were grazing. Bulk milk samples were collected on 12 consecutive days at two sampling periods: in indoor and in grazing months and analysed for milk compositions and vitamin A, E and D 3 , as well as for fatty acid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The average PUFA n6/PUFA n3 ratio was similar to the results shown by Pajor et al (2014) for extensively grazing goat. In the past different values of PUFA n6/ PUFA n3 for a healthy diet have been proposed.…”
Section: Discussionsupporting
confidence: 86%
“…The average PUFA n6/PUFA n3 ratio was similar to the results shown by Pajor et al (2014) for extensively grazing goat. In the past different values of PUFA n6/ PUFA n3 for a healthy diet have been proposed.…”
Section: Discussionsupporting
confidence: 86%
“…Malissiove et al (2015) found no significant differences. On the other hand, Tudisco et al (2010) and Bovera et al (2007) recorded higher fat content in organic milk, while Pajor et al (2014) apart from the fat, found higher protein content and nonfat dry matter in organic goat milk.…”
Section: Introductionmentioning
confidence: 90%
“…The chemical form of mineral elements is important because it determines their absorption in the intestine and their biological utilization (Zamberlin et al, 2012). The quantity and quality of milk production as well as the concentration of nutrients and minerals in milk depends on many factors such as the genetic (Miluchová et al, 2014;Trakovická et al, 2015); lactation stage (Kuchtík et al, 2015;Pavlata et al, 2016); health status (Vlček et al, 2016); bud the main factor is nutrition (Pajor et al, 2014;Tudisco et al, 2014). Nowadays the concentration of minerals in food is an important factor of human nutrition and health.…”
Section: Introductionmentioning
confidence: 99%